2022
DOI: 10.1590/1980-265x-tce-2021-0350en
|View full text |Cite
|
Sign up to set email alerts
|

Professional Attitudes Towards Suicidal Behavior in Primary Health Care: A Quasi-Experimental Study

Abstract: Objective: to analyze the attitudes of health professionals working in Primary Health Care before and after participating in workshops about how to approach people with suicidal behavior. Method: a before-and-after quantitative and quasi-experimental study, conducted in a municipality in the inland of the state of São Paulo from August to September 2019. The sample consisted of 34 workers who answered a Sociodemographic Questionnaire and the Questionnaire on Attitudes towards Suicidal Behavior, applied befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Beyond knowledge and skills, studies have shown that nurses' attitudes can have a significant impact on the quality of care and patient treatment. Research has shown that nurses and primary physicians who hold stigmatizing attitudes and negative beliefs toward mental illness and suicide may be less attuned to warning signs of depression or suicide risk among their patients, and fail to provide appropriate care, such as referral to mental health services or crisis intervention [15,47]. Furthermore, research has consistently demonstrated that healthcare providers tend to hold pessimistic views about the reality and the prospects of recovery, leading them to believe that "what they do doesn't matter" [48].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond knowledge and skills, studies have shown that nurses' attitudes can have a significant impact on the quality of care and patient treatment. Research has shown that nurses and primary physicians who hold stigmatizing attitudes and negative beliefs toward mental illness and suicide may be less attuned to warning signs of depression or suicide risk among their patients, and fail to provide appropriate care, such as referral to mental health services or crisis intervention [15,47]. Furthermore, research has consistently demonstrated that healthcare providers tend to hold pessimistic views about the reality and the prospects of recovery, leading them to believe that "what they do doesn't matter" [48].…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, podemos afirmar que quando há um contato desses estudantes, com demandas suicidas em sua formação, a chance de desenvolvermos profissionais mais qualificados nesta temática, aumenta significativamente, contribuindo para a construção de novos conhecimentos e a desconstrução de crenças negativas que impedem um tratamento mais preciso e eficaz [9].…”
Section: Nas Pesquisas De Campo O Tamanho Das Amostras Variou De 10 à...unclassified
“…Treinamento adequado e constantes informações sobre o tema é importante para o aprimoramento dos comportamentos e atitudes adotadas pelos profissionais, proporcionando o aumento das habilidades para respostas clínicas compatíveis que permitam a avaliação e gerenciamento de riscos, viabilizando a interação com estes pacientes [9].…”
Section: Conclusãounclassified